Global mental health: transformative capacity building in Nicaragua - Jaime C. Sapag; Andrés Herrera; Ruth Trainor; Trinidad Caldera; Akwatu Khenti (Taylor & Francis Group, 2013)
Background: Mental health is increasingly recognised as integral to good public health, but this area continues to lack sufficient planning, resources, and global strategy. It is a pressing concern in Latin America, where social determinants of health aggravate existing inequities in access to health services. Nicaragua faces serious mental health needs and challenges. One key strategy for addressing gaps in mental health services is building capacity at the primary healthcare and system levels. Objective: Using the framework of best practice literature, this article analyses the four-year collaborative process between the National Autonomous University of Nicaragua in León (UNAN-León) and the Centre for Addiction and Mental Health (CAMH) in Canada, which is aimed at improving mental healthcare in Nicaragua. Design: Based on a critical analysis of evaluation reports, key documents, and discussion among partners, the central steps of the collaboration are analysed and main successes and challenges identified. Results: A participatory needs assessment identified local strengths and weaknesses, expected outcomes regarding competencies, and possible methodologies and recommendations for the development of a comprehensive capacity-building programme. The partners delivered two international workshops on mental health and addiction with an emphasis on primary healthcare. More recently, an innovative Diploma and Master programme was launched to foster interprofessional leadership and effective action to address mental health and addiction needs. Collaborative activities have taken place in Nicaragua and Canada. Discussion: To date, international collaboration between Nicaragua and CAMH has been successful in achieving the jointly defined goals. The process has led to mutual knowledge sharing, strong networking, and extensive educational opportunities. Evidence of effective and respectful global health capacity building is provided. Lessons learned and implications for global health action are identified and discussed.